(untitled) (Universal International Scientific Journal, 2026)
This article discusses the content and essence of pedagogical erudition, its role in the training of highly qualified educators, and its integration with visual activity classes in the educational process. The article analyzes practical ways to form pedagogical erudition, develop children’s creative abilities through visual activity, and increase the professional competence of teachers.